Evaluation of the relationship of mucous retention cyst with the restoration and loss situations of the teeth adjacent to the maxillary sinus with panoramic radiographs - Baybars, Sümeyye Coşgun; Türkcan, Mehmet Buğra (Gazi Üniversitesi, 2025)
Objective: This study aims to evaluate whether the restoration and loss of teeth adjacent to the maxillary sinuses affect the formation of mucous retention cysts by examining the panoramic radiographs of patients who came to Fırat University Faculty of Dentistry for various reasons. Materials and Method: In the study, the panoramic radiographs of a total of 1585 patients, 863 women and 722 men, aged 18–65, who came to Fırat University Faculty of Dentistry for treatment between 2021 and 2022 were retrospectively examined. Existing restorations such as root canal treatment, filling, and crown on the upper first premolar, upper second premolar, upper first molar, and upper second molar teeth that are in relation to the maxillary sinuses, restoration need (canal treatment, filling, crown, caries), and loss status were determined. SPSS (SPSS® v22.0; SPSS Inc.,Chicago, USA) program was used to analyze the data obtained statistically. The data were analyzed using the Pearson Chi-Square test and the Bonferroni method. p

Amaç: Bu çalışmada, Fırat Üniversitesi Diş Hekimliği Fakültesi’ne çeşitli sebeplerle gelen hastaların panoramik radyografileri incelenerek; maksillar sinüse komşu dişlerin restorasyon ve kayıp durumlarının mukos retansiyon kisti oluşumuna etkisi olup olmadığının değerlendirilmesi amaçlanmaktadır. Gereç ve Yöntem: Çalışmada, 2021-2022 yılları arasında Fırat Üniversitesi Diş Hekimliği Fakültesi’ne tedavi için gelen, 18-65 yaş aralığında bulunan, 863’ü kadın, 722’si erkek toplam 1585 hastanın panoramik radyografı retrospektif olarak incelendi. Maksillar sinüs ile ilişkisi olan üst birinci premolar, üst ikinci premolar, üst birinci molar, üst ikinci molar dişlerdeki, kanal tedavisi, dolgu, kaplama olan mevcut restorasyon, restorasyon ihtiyacı (kanal tedavisi, dolgu, kaplama, çürük) ve kayıp durumu tespit edilip kaydedildi. Elde edilen verilen istatistiksel analizi için SPSS (SPSS® v22.0; SPSS Inc., Chicago, USA) programı kullanıldı. Veriler Pearson Ki-kare testi ve Benferroni metodu kullanılarak değerlendirildi. P
Mukos retansiyon kistinin maksillar sinüse komşu dişlerdeki restorasyon ve kayıp durumlarıyla ilişkisinin panoramik radyograflarla değerlendirilmesi
Keywords: Oral and Maxillofacial Radiology; Ağız; Diş ve Çene Radyolojisi